Systematic Literature Review on the Utilization of Tuber Crop Skins in the Context of Circular Agriculture - Aziz Caliskan; Norhidayah Abdullah; Noriza Ishak; Divine Senanu Ametefe; Imene Tatar Caliskan (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This Systematic Literature Review (SLR) investigates the utilization of tuber crop skins, specifically from yam, potato, taro, and cassava as an underexplored resource in circular agriculture. The study aims to assess their multifaceted applications across sectors such as animal feed, bioenergy, material science, wastewater treatment, and food innovation, addressing the overarching research question of how tuber crop skins can contribute to a more sustainable agricultural model.